The Position and Development of Photocopy Evidence in the Evidence Process Based on the Jurisprudence of the Indonesian Supreme Court - Rahmat, Riris Risnayanti; Sari, Lucky Nurlita; Tejo, Eko Susanto; Juliawati, Kania; Gunawan, Verawati; Rahayu, Mega; Yogapranatha, Andrian; Fakhriah, Prof. Dr. Efa Laela; Santoso, Edy (International Journal of Scientific Research and Management (IJSRM), 2025)
The process of proof is the most specific and most decisive stage in a civil case. Proof is an effort by the parties to the case to convince the judge of the truth of the events submitted by the parties by using evidence stipulated by law. In practice, it is often found that the use of photocopy evidence is not available in the original document or cannot be matched with the original document, such as in case number 329/Pdt.G/2021/PN.Sby. The author examines the role of judges in examining cases that use photocopy evidence and do not have the original, as well as the position of jurisprudence as a reference in the evidence process in court. This study uses a normative-empirical legal approach, analytical descriptive research specifications, and qualitative normative data analysis. The results of the study and discussion concluded that judges play an important role in examining, assessing the strength, and validity of the evidence submitted by the parties to the case by referring to applicable legal sources. The position of jurisprudence is as one of the sources of law, although jurisprudence is not binding on judges, the existence of jurisprudence is a guideline for judges who aim to maintain consistency and prevent disparities in decisions in similar cases.